1996
DOI: 10.1002/(sici)1098-2744(199603)15:3<190::aid-mc5>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Connexin expression in epidermal cell lines from SENCAR mouse skin tumors

Abstract: Alteration of gap-junctional intercellular communication (GJIC) has long been proposed to be involved in carcinogenesis. Previously, we reported that the level of gap junctional intercellular communication in mouse skin carcinoma cell lines is significantly lower than in papilloma cell lines and normal mouse keratinocytes Klann et al., Cancer Res 49:699-705, 1989). Here, we present data on expression of the gap-junctional protein connexins (Cx) 26, Cx31.1, and Cx43 in a comprehensive panel of keratinocyte cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Tumor progression, including the loss of differentiation, invasion, and metastasis, is associated with a quantitative and qualitative gradual decrease in expression of Cx43, Cx26, and Cx31.1 during multistage mouse skin carcinogenesis. Analysis of the expression pattern and gap junctional permeability in this model system suggests a differential regulation of each Cx gene during tumorigenesis, the mechanisms of which are still largely unknown (71,83,85). Recent data point to a possible inactivation of Cxs by hypermethylation of their promotor region, aberrant intracellular localization, or alternatively, disruption of various functional control mechanisms (86) (89)(90)(91).…”
Section: The Role Of Connexins In Growth Control and Tumorigenesismentioning
confidence: 89%
“…Tumor progression, including the loss of differentiation, invasion, and metastasis, is associated with a quantitative and qualitative gradual decrease in expression of Cx43, Cx26, and Cx31.1 during multistage mouse skin carcinogenesis. Analysis of the expression pattern and gap junctional permeability in this model system suggests a differential regulation of each Cx gene during tumorigenesis, the mechanisms of which are still largely unknown (71,83,85). Recent data point to a possible inactivation of Cxs by hypermethylation of their promotor region, aberrant intracellular localization, or alternatively, disruption of various functional control mechanisms (86) (89)(90)(91).…”
Section: The Role Of Connexins In Growth Control and Tumorigenesismentioning
confidence: 89%
“…reported that Cx31.1 was down‐regulated in head and neck squamous cell carcinoma [25]. Budunova et al found that all the epidermal cell lines from SENCAR mouse skin tumours they studied were Cx31.1 negative [26]. To our knowledge, there is no report about the association between Cx31.1 and lung cancer carcinogenesis and metastasis as yet.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the Neigborhood Coherence Principle (NCP), described by Phipps et al [67,68], which suggests that a system of interacting cells can produce and maintain homeostasis by virtue of cell‐cell communication. In support of the NCP, several studies have shown that any decrease or disconnection in GJIC would allow some cells with proliferative potential to resume their mitotic activity [15,69–74]. This proliferative potential is associated with the lack of differentiation, which is one of the hallmarks of NB [9].…”
Section: Discussionmentioning
confidence: 99%